2022
DOI: 10.1039/d2fo01178f
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fiber ameliorates sleep disturbance connected to the gut–brain axis

Abstract: Circadian rhythms play an important role in maintaining normal physiological and psychological functions of the body, including regulating sleep patterns. External factors such as poor eating habits and work and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Dietary fiber may improve sleep disorders from the perspective of the brain–gut axis or brain–gut–microbiota axis [ 27 ]. Dietary fiber can be divided into soluble and insoluble types.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dietary fiber may improve sleep disorders from the perspective of the brain–gut axis or brain–gut–microbiota axis [ 27 ]. Dietary fiber can be divided into soluble and insoluble types.…”
Section: Discussionmentioning
confidence: 99%
“…SCFAs are mainly produced by Bifidobacterium, Lactobacillus, Rosetella, Bacteroidetes, and Firmicutes spp. [ 27 ]. SCFAs promote the secretion of serotonin (5-hydroxytryptamine) from the enterochromaffin cells, increasing the level of sleep aids in the body [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that the gut microbiota acts on intestinal chromaffin cells using SCFAs as mediators, regulating the synthesis and release of 5-HT. SCFAs promote the secretion and release of 5-HT and induce peristaltic reflex, thereby enhancing colonic contraction and accelerating colonic transport (23). Therefore, butyrate-producing bacteria in feces are associated with rapid colonic transport.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have demonstrated that SCFAs ameliorate sleep disturbance through immune, neural, and endocrine pathways [ 129 ]. Significant alterations in the clock gene were observed both in animal models of PD and in patients [ 130 ].…”
Section: Scfas and Non-motor Symptoms Of Pdmentioning
confidence: 99%